Quality by Design Based Formulation Study of Meloxicam-Loaded Polymeric Micelles for Intranasal Administration - Bence Sipos; Piroska Szabó-Révész; Ildikó Csóka; Edina Pallagi; Dorina Gabriella Dobó; Péter Bélteky; Zoltán Kónya; Ágota Deák; László Janovák; Gábor Katona (MDPI AG, 2020)
Our study aimed to develop an "ex tempore" reconstitutable, viscosity enhancer- and preservative-free meloxicam (MEL)-loaded polymeric micelle formulation, via Quality by Design (QbD) approach, exploiting the nose-to-brain pathway, as a suitable tool in the treatment of neuroinflammation. The anti-neuroinflammatory effect of nose-to-brain NSAID polymeric micelles was not studied previously, therefore its investigation is promising. Critical product parameters, encapsulation efficiency (89.4%), Z-average (101.22 ± 2.8 nm) and polydispersity index (0.149 ± 0.7) and zeta potential (−25.2 ± 0.4 mV) met the requirements of the intranasal drug delivery system (nanoDDS) and the targeted profile liquid formulation was transformed into a solid preservative-free product by freeze-drying. The viscosity (32.5 ± 0.28 mPas) and hypotonic osmolality (240 mOsmol/L) of the reconstituted formulation provides proper and enhanced absorption and probably guarantees the administration of the liquid dosage form (nasal drop and spray). The developed formulation resulted in more than 20 times faster MEL dissolution rate and five-fold higher nasal permeability compared to starting MEL. The prediction of IVIVC confirmed the great potential for in vivo brain distribution of MEL. The nose-to-brain delivery of NSAIDs such as MEL by means of nanoDDS as polymeric micelles offers an innovative opportunity to treat neuroinflammation more effectively.